Cognitive enhancement in video game players: The role of video game genre. (March 2015) - Dobrowolski, Pawel; Hanusz, Krzysztof; Sobczyk, Bartosz; Skorko, Maciek; Wiatrow, Andrzej
Highlights: We compare first-person shooter and real-time strategy video game players. Action video games provide differential benefits to cognition depending on genre. Real-time strategy players show superior performance on multiple object tracking. Game mechanics may determine occurrence of specific cognitive enhancements. Abstract: Several cross-section and training studies have shown that video game play can improve cognitive functions such as visual attention, cognitive control, visual short-term memory, and general processing speed. Unfortunately the replication of these effects is not always successful, even when using similar cognitive tests to measure performance. We investigated an important aspect of this field that has not yet been empirically addressed: the role of video game genre. Our comparison of two video game player groups of specific genres (first-person shooter and real-time strategy) indicates that cognitive abilities (measured by task switching and multiple object tracking) may be differentially enhanced depending on the genre of video game being played. This result is significant as research to this point has focused on "action video games", a loosely defined category that encompasses several video game genres, without controlling for effects potentially stemming from differences in mechanics between these video games. It also provides some evidence for the specificity of video game play benefits as a function of actions performed within the game, which is not in line with a generalized "learning to learn" accounting of these enhancements.